Kombucha: From introduction and healing properties to being Halal - Kianoosh Khosravi Darani (Halal Research Center of Islamic Republic of Iran, 2021)
Background and purpose: The popularity of fermented beverages is increasing due to the preservation of food value and health characteristics of the product during fermentation. Kombucha is a probiotic and beneficial fermented beverage obtained from the social coexistence of bacteria and osmophilic yeasts in a sweetened black tea environment with sucrose. Sucrose is hydrolyzed to glucose and fructose by the invertase enzyme produced by the yeasts in the Kombucha consortium, and fructose is converted to ethanol and carbon dioxide by the yeasts. Despite the excellent health benefits of this drink, it can sometimes be controversial due to the increase in ethanol levels and the issue of halal quality. Results: The final concentration of ethanol alcohol in kombucha varies depending on parameters such as the species of microorganisms present in the solution, temperature, fermentation time and the initial sugar consumption. Using measurements such as controlling the amount of consumed sucrose, regular aeration during the fermentation process, using green and black tea as a substrate, using certain species of microorganisms to reduce the amount of ethanol produced, reducing the pH of the solution during the process and using Alternative sources of sucrose with lower sweetness such as honey and berry juice, can reduce the amount of ethanol produced in kombucha by 0.5%. Conclusion: Kombucha with an alcohol content of less than 3% is considered a non-alcoholic beverage. Using simple and practical solutions, the amount of ethanol produced in the Kombucha solution can be significantly reduced and the miraculous properties of this drink can be benefited.